EXPLORING RELIGIOUS AND RITUAL VOCABULARY THROUGH CULTURAL SEMANTICS - Muhammad Natsir (Social Studies and Humanities Journal (SOSHUM), 2025)
Language reflects cultural values ​​and beliefs, yet thousands of languages ​​are endangered, threatening cultural heritage, including religious and ritual vocabulary. This study explores the role of cultural schemas and conceptual metaphors in shaping the meaning of religious and ritual vocabulary, confirming that religious language is a profound reflection of a community's cultural values ​​and beliefs. Using narrative review Using data from Scopus, Web of Science, LLBA, and Google Scholar, this study analyzes literature published between 2010 and 2025, focusing on cognitive linguistics, cultural linguistics, and language-religion studies. The analytical framework involvesCultural Conceptualization Analysis(CCA) andSemantic Field Analysis. The results indicate that cultural schemas (e.g., purity, sanctity, sacrifice) serve as conceptual frameworks that organize the interpretation of religious terms, distinguishing them from everyday language. Conceptual metaphors, such as "RELIGION AS A JOURNEY," are fundamental frameworks for understanding abstract theological concepts. Ritual vocabulary also exhibits semantic dynamics, with meanings expanding according to cultural context. These findings strengthen Cultural Linguistics and Semantic Field Theory, providing empirical evidence of the interrelationship between cultural schemas and religious semantic structures. Practically, this understanding is crucial for accurate translation of sacred texts, effective interfaith communication, and the preservation of minority languages ​​rich in cultural meaning. However, research is still dominated by theoretical approaches and a focus on majority languages. Future studies should integrate interdisciplinary methods, including corpus analysis and fieldwork, as well as cross-cultural comparative analysis for a more comprehensive understanding.